2008
DOI: 10.3174/ajnr.a1404
|View full text |Cite
|
Sign up to set email alerts
|

CT Imaging of Head and Neck Lupus Panniculitis

Abstract: SUMMARY:Lupus panniculitis (LP) or lupus erythematosus profundus (LEP) is a lupus-associated dermatologic condition predominantly affecting young to middle-aged women in which the deep dermis and subcutaneous fat are mainly involved. The lesions are usually located on the forehead, cheeks, proximal aspect of the limbs, and buttocks, though cases have occasionally been reported with orbital, breast, and salivary gland involvement. Descriptions of imaging findings of LP are very scarce in the literature. We desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…In LEP the overlying skin appears normal while the deep dermis and subcutaneous fat is involved by the inflammatory process. 1, 2 LEP usually presents in isolation. Only 2–5% of patients with discoid or systemic lupus also have LEP.…”
Section: 3 Discussionmentioning
confidence: 99%
“…In LEP the overlying skin appears normal while the deep dermis and subcutaneous fat is involved by the inflammatory process. 1, 2 LEP usually presents in isolation. Only 2–5% of patients with discoid or systemic lupus also have LEP.…”
Section: 3 Discussionmentioning
confidence: 99%
“…Two earlier case reports suggested that subcutaneous LP lesions may be detected by a CT scan. [10,11] However, CT findings in our patient were unremarkable, despite the presence of extensive subcutaneous inflammation. Our report therefore suggests that an FDG-PET/CT scan might be more appropriate for identifying LP lesions than a CT scan.…”
Section: Discussionmentioning
confidence: 62%
“…These nodules and plaques are usually located on the forehead, cheeks, extremities, and buttocks. They have occasionally been reported to affect the orbit 11 . The main treatment option for orbital and external eye disease is systemic hydroxychloroquine therapy.…”
Section: Orbital and External Eye Diseasementioning
confidence: 99%